Analysis of Project-Based Learning Models in Improving Students' Understanding of Science Learning - Andawiyah, Khoirun Nisa’; Harianto, Rony; Nurdiantami, Yuri (Program Studi Tadris IPA, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
Students often have difficulty understanding science concepts in depth because learning is still centered on lecturers. The project-based learning (PjBL) model is an approach that emphasizes the active involvement of students in completing tasks relevant to real-world contexts. This study aims to analyze the effectiveness of the PjBL model in improving students' understanding of science learning materials. The research method employed a qualitative approach, utilizing data collection techniques through interviews and questionnaires with 36 students from the Tadris IPA Study Program in their fourth semester at UIN Madura. The results showed that the majority of students felt an increase in conceptual understanding, critical thinking skills, and collaborative skills after participating in project-based learning. These finding suggest that the PjBL model can be an effective alternative for enhancing the quality of science learning in higher education.